Vector analysis: vector algebra and vector calculus - Ghosh, Ram Krishna; Maity, Kantish Chandra (Kolkata: New Central Book Agency (P) Ltd., 2003)
The present treatise on vector analysis is intended to be a textbook for undergraduate classes in Indian universities. The notion of a vector has been approached from two points of view - geometric and algebraic. A correspondence between the two has also been established. It has been the aim of the authors to make available to the readers a tool of which he may make a profitable use in his studies of the various branches of mathematics, and of analytic geometry and mechanics, in particular.
Elementary Operations: Centroids -- Applications of Elementary Operations: Geometrical and Physical -- Product of Vectors -- Applications of Vector Products to Space Geometry -- Differentiation And Integration of Vectors: Scalar and Vector Fields -- Elements of Differential Geometry -- Applications Of Vector Calculus in Mechanics -- Gradient, Divergence and Curl --Vector Integration: line , surface and volume Integrals --the divergence theorem of Gauss, Stokes' theorem and Green's theorem
Includes index
Keywords: Vector Algebra; Vector Calculus